A CASE OF MULTIPLE TRAUMA INVOLVING ADRENAL INJURY SUCCESSFULLY TREATED USING GAUZE PACKING - NORIMOTO, Kazunobu; OKUCHI, Kazuo; IWAMURA, Asami; KAWAI, Yasuyuki; MIYAZAKI, Keita; INOUE, Gou; KITAOKA, Hironori; TADA, Yusuke; SEKI, Tadahiko; FUKUSIMA, Hidetada; HATA, Michiaki (Journal of the Japanese Association for the Surgery of Trauma, 2014)
This report presents a case of adrenal injury with active bleeding that was treated using gauze packing. A 21-year-old man who had been involved in a motor vehicle accident was transferred to our hospital. Abdominal contrast-enhanced computed tomography revealed lung injuries, liver injuries, right renal injury, and adrenal injury with active bleeding ; therefore, an emergency laparotomy was performed. The retroperitoneal pressure suppressed the bleeding due to the adrenal injury. However, dissection into the retroperitoneum to repair the renal injury resulted in loss of the compressive effect of the adjacent structures ; therefore, the adrenal injury had to be repaired along with the hepatic injury. Gauze packing was effective, and aortography did not reveal any extravasation. The findings of this case, suggest that gauze packing should be considered for treating adrenal injury with active bleeding, especially in cases in which open surgery is performed before angiography.